Estimation of the quality of life in patients with prostate cancer hospitalized during radical radiotherapy treatment. Part I - Nowicki, Andrzej; Staniewska, Jadwiga; Tesmer, Izabela (Contemporary Oncology/Współczesna Onkologia, 2007)
Introduction: Prostate cancer is the most frequent tumour of the urinary-sexual system among men. The choice of therapy depends mainly on the side effects. Objectives: The general assessment of quality of life in patients with prostate cancer during radical radiotherapy was the main goal of this work. Material and methods: Our survey includes 26 men aged 53-86 (median 69) with the diagnosis of prostate cancer treated with conformal radical radiotherapy under hospital conditions. The treatment was conducted using X photons produced by a linear accelerator, 5 times a week with 2 days pause on average. Average overall time of treatment was 6.5 weeks (which made 33 fractions on average). The average dose of radiation was 66 Gy per patient. To assess the radiotherapy effect on patient’s quality of life, the quality of life before treatment (A1 group) and at the end of treatment (A2 group) were assessed. Standard questionnaire EORTC QLQ - C30 (version 3.0), created by the European Group of Life Quality Studies for oncological patients were used for this purpose. Results: We observed serious perturbations in the domain of social life of all others areas of life in patients with prostate cancer during radiotherapy. Perturbations in family life were observed most frequently and occurred in 19.23% of patients in group A2 (median point-rate was 1.46 for group A1 and 1.92 for group A2). In the area of symptoms, the need for rest was the most frequent sign of fatigue, which was often felt by 23.08% of patients and very often by 3.85% of patients at the end of the treatment period. A problem related to insomnia was an important matter in this area and occurred among 15.38 % of patients in group A2 and was very important in 11.54% of patients. General assessment of quality of life was correlated with lower rate of health condition; median point-rate was 5.07 for group A1 and 4.62 for group A2. Conclusions: Radiotherapy among patients with prostate cancer hospitalized during the early treatment period did not disturb the majority of areas of life. Until the end of therapy patients maintained normal outdoor physical activity, cognitive and emotional functions, and they fulfilled their roles in everyday life. During the treatment patients felt tired, had problems with sleep and needed rest more often. Social functioning was significantly disturbed mainly in their family life. General quality of life after treatment was lower together with worse health condition rate.